Ethnomathematics exploration of Al-Barkah Great Mosque, Bekasi City, through geometry and transformational geometry learning - Soebagyo, Joko; Luthfiyyah, Fadhilah Izzul (Indonesian Journal of Science and Mathematics Education, 2023)
Ethnomathematics integrates cultural elements into mathematics learning, fostering students' conceptual understanding while preserving cultural heritage. Ethnomathematics in religious architecture offers a unique perspective on the relationship between mathematical concepts and cultural values. This study aims to explore the ethnomathematical aspects of the Al-Barkah Great Mosque in Bekasi by analyzing its symbolic and geometric elements. A qualitative research approach with a realist ethnographic method was employed, incorporating interviews, observations, documentation, and literature reviews to examine the mathematical structures embedded in the mosque’s architectural design. The findings reveal that the Al-Barkah Great Mosque exhibits various geometric shapes and transformation elements, including reflection, rotation, and translation, which hold both cultural and spiritual significance. These mathematical features serve as concrete representations that enhance students' comprehension of geometric concepts. The study concludes that integrating ethnomathematics into geometry learning provides an engaging and meaningful context for students, connecting mathematical theories with real-world cultural artifacts. The implications of this study include enriching geometry instruction through cultural perspectives and providing educators with culturally relevant resources to enhance student learning and appreciation of mathematical concepts.